(untitled) (Global Journal of Medical Research, 2016)
Background Spinal cord injury SCI is a multisystem injury with life-threatening complications Bone demineralization renal complications have serious consequences for the affected person It is hypothesized that verticalisation along with early mobilization reduces skeletal renal complications Methodology 48 subjects 36 patients 12 controls participated in this study The patients were divided into groups A B C and the controls were in Group D Basal parameters BP PR RR were recorded and Urine samples were sent for analysis Group A was treated with only limb exercises Group B was given limb exercises tilt table standing Group C had chronic patients to visualize the longterm effect of physical rehabilitation body s attempt at bone mineral homeostasis on urinary parameters Results Significant changes were noted in the values of urine calcium inorganic phosphate hydroxyproline serum enzyme alkaline phosphatase among groups A B C when compare with D